Wound Closure in Flexion versus Extension following Total Knee Replacement: Outcomes and Complications - Mahmood, Aatif; Fursdon, Thomas; Peter, Viju; Kumar, Gunasekaran (The Journal of Knee Surgery, 2019)
Position of the knee may affect the range of movement (ROM) after a total knee replacement (TKR). It has been postulated that wound closure in extension may cause shortening of the extensor mechanism and increased tension on the soft tissues. The aim of this study was to determine effect of wound closure in TKR with the knee in flexion or extension on postoperative ROM and rehabilitation. A consecutive series of 121 patients underwent primary TKR between May 2011 and August 2012. Group A (60 patients) had wound closure in extension. Group B (61 patients) had wound closure in flexion. Baseline demographic data were compared—age, body mass index, gender, American Society of Anesthetists status, length of stay, wound healing, and ROM. Oxford Knee Score (OKS) were assessed at 6 months, 1 year, and 2 years. Fifty-two males and 69 females with average age of 68 years (32–86) underwent TKR. There were no wound complications requiring surgical intervention. One patient in each group required manipulation under anesthesia for stiffness. There was no statistical difference in ROM and OKS at the last follow-up. There was no difference in outcomes following knee closure in flexion or extension.
Keywords: total knee replacement; wound closure; range of movement